3D kinematic analysis of slalom elite skiers at the Bormio World Cup ski finals in 2008 - Pozzo, R.; Canclini, A.; Baroni, G.; Canclini, A. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The definition of meaningful biomechanical models of alpine skiing technique turns out to be a much more difficult challenge than the parametric modelling frequently used in other sports. Nevertheless, the kinematic and kinetic motion description during high level competitions can provide fundamental information towards the quantitative evaluation of the biomechanical constrains which influence the performances. Provided the limited amount of studies reporting movement kinematics during ski competitions, we focused our work on collecting three-dimensional kinematics data on athletes during a World Cup Slalom race.